Quality of Life in Patients With Breast Cancer: The Influence of Family Caregiver's Burden and the Mediation of Patient's Anxiety and Depression. Issue 11 (November 2019) - An, Yuanyuan; Fu, Gan; Yuan, Guangzhe
Abstract : Abstract: Previous research showed that family caregiver's perception of burden can influence patient's report on their quality of life (QoL). The present study investigated the relationship between the two variables by considering the role of patient's anxiety and depression. A total of 382 dyads of Chinese breast cancer patients and their family caregivers participated in this study. The results showed that the mediation model fitted the data well (χ 2 = 49.859; df = 16; χ 2 / df = 3.116; RMSEA = 0.05; TLI = 0.928; CFI = 0.959). It indicated that family caregiver's burden influenced patient's QoL negatively, and this relationship was partially mediated by patient's anxiety and depression.